DESIGN OF DUMP TRUCK SIMULATION CONTROL AREA NETWORK USING THE SPI CAN MODULE, A PIC 18F452 AND PIC 16F877 - Ardi, Syahril; Rahmandanu, Titis Sondha (LPPM Politeknik Astra, 2012)
In the units of heavy equipment such as dump trucks have a wide range of electrical controls communicate with each other. Communication between the control-based communication systems using Control Area Network (CAN). To support the training activities then made control area network simulation equipment. The simulation equipment simulates multiple existing controls on the units of heavy equipment, namely: control monitor, control engine, and transmission control. In this study the design of simulation equipments have been developed Control Area Network (CAN) monitor, engine and transmission. The design of this simulation equipment using a PIC 18F452 microcontroller as the brains for the control monitor and PIC 16F877 as the brains for the control engine, and transmission. Communication in this simulation equipment to use CAN-SPI module. The third control has input, output, and its own function. Control monitor has a function as a monitor of the other control conditions such as rpm, temperature, and throttle position. Control engine functions as a regulator of rpm and has an indicator of ignition. Transmission control functions as a modifier of transmission mode, has a level indicator of the transmission, and has a temperature sensor to monitor ambient temperature.